The Word Frequency Effect on Saccade Targeting during Chinese Reading: Evidence from a Survival Analysis of Saccade Length - Liu, Yanping; Huang, Ren; Li, Yugang; Gao, Dingguo (Frontiers in Psychology, 2017)
Our study employs distributional analysis (i.e., survival analysis) to examine how the frequency of target words influences saccade lengths into and out of these target words in Chinese reading. The results of survival analysis indicate the survival curves in the high- and low-frequency conditions diverge for a short saccade length, with more than 80% of the lengths of incoming and outgoing saccades being larger than the divergence points. These results as well as simulations using the novel Dynamic-adjustment Model of saccadic targeting (Liu, Reichle, & Li, 2016) are consistent with previous mean-based results and provide more precise information to support this novel model. The implications for saccade target selection during the reading of Chinese are discussed.